2017
DOI: 10.1111/spol.12295
|View full text |Cite
|
Sign up to set email alerts
|

Receipt of Formal and Informal Help with Specific Care Tasks among Older People Living in their Own Home. National Trends over Two Decades

Abstract: Sweden is seen as a typical example of a social democratic welfare regime, with universal and generous welfare policies. However, in the last decades, there have been substantial reductions in the Swedish provision of care for older people. This study aimed to examine trends in sources of care-receipt in older people (77+) living in their own home and with a perceived need for help with two specific tasks: house cleaning and/or food shopping. Trends in care-receipt were examined in relation to gender, living a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 45 publications
3
31
1
Order By: Relevance
“…34 Yet, when relationships last into advanced old age, the capacity of caring for a partner toward the end of life, when care needs often are extensive, may be limited among very old couples. Against the background of recent developments in the Swedish LTC system, it may be expected that support from family members outside the household will gain importance, 25,35 as well as services paid out of pocket, indicating a narrower definition of public responsibility. 25,33,36…”
Section: Discussionmentioning
confidence: 99%
“…34 Yet, when relationships last into advanced old age, the capacity of caring for a partner toward the end of life, when care needs often are extensive, may be limited among very old couples. Against the background of recent developments in the Swedish LTC system, it may be expected that support from family members outside the household will gain importance, 25,35 as well as services paid out of pocket, indicating a narrower definition of public responsibility. 25,33,36…”
Section: Discussionmentioning
confidence: 99%
“…About 37% of older Swedes provide informal help to family, friends or neighbours (Hank & Stuck, ) and about 52% identify themselves as informal helpers for a person outside their own homes (Jegermalm & Jeppsson Grassman, ). In an international comparison, spending on elderly care in Sweden is fairly high; however, as provisions of formal care have not kept pace with the ageing population (Rostgaard & Szebehely, ; Szebehely & Trydegård, ), many older people rely on informal care (Dahlberg, Berndt, Lennartsson, & Schön, ). Altogether, Sweden is a suitable setting to explore care practices among older people.…”
Section: Methodsmentioning
confidence: 99%
“…Providing adequate nutritional care, i.e., support with shopping, preparing meals, eating and drinking, for this frail group seems to be crucial, but may be required in varying degrees, depending on the overall need of care, and may be provided by different people and services. It has been shown in a study on older adults living at home and being in need of care in Sweden that those who did not live alone received more nutritional care from their informal caregivers compared to those who lived alone [6]. Another study also from Sweden similarly reported that informal caregivers are the primary source of providing nutritional care and support in older adults living in private households [21].…”
Section: Introductionmentioning
confidence: 99%
“…Most older adults are willing to spend their last years of life in their own household [2]. Previous studies in several European countries have shown that more than half of the older adults receiving care at home are living alone [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%